Issues for further consideration concerning digital sequence information: a submission from CGIAR - CGIAR (2023)
CGIAR made this written submission to the CBD (Convention on Biological Diversity) Open-Ended Working Group on Benefit-Sharing from the Use of Digital Sequence Information on Genetic Resources, in response to the CBD Secretariat’s call for a “Submission of views on issues for further consideration for digital sequence information” (CBD Notification 2023-023). The call requested targeted feedback with respect to sixteen issues, as identified by the 15th Session of the Conference of the Parties to the CBD (COP 15) in Decision 15/9, for further consideration.